Deixis in Indonesian Short Movie "Aku dan Mesin Waktu" - Putri Sinta Dewi, Ni Made (JLER (Journal of Language Education Research), 2025)
This study aimed at analyzing the deixis used in Indonesian short movie Aku dan Mesin Waktu. This short movie was directed by the famous film director Upie Guava that released in 2022. The data was taken from the dialogues of the actors and actresses of the short movie Aku dan Mesin Waktu. The data was collected with a qualitative method. The data was analyzed using Yule’s theory. The result denoted that the three types of deixis according to Yule’s theory were found. The total of the data collected is 192 data. The deixis that is used the most in this short movie is person deixis with 155 words spoken that is classified into three categories; first person, second person, and third person. The second is the temporal deixis in total 30 words, and the least used is spatial deixis with 7 words spoken. Furthermore, this research is expected to give more understanding of deixis in an Indonesian short movie.